Influence of restrainer bar chairs on the compression and flexural behaviour of reinforced masonry walls. (January 2022) - Zahra, Tatheer; Asad, Mohammad; Thamboo, Julian; Noor-E-Khuda, Sarkar; Derakhshan, Hossein
Abstract: Lateral restrainers are traditionally provided in reinforced masonry (RM) walls to prevent the vertical steel bars from buckling. In the current version of the Australian Masonry Standards (AS 3700–2018), the use of lateral restrainers in RM walls is relaxed, if the vertical rebars are surrounded by grout annulus of twice the diameter of the bars. However, it is challenging to maintain the verticality of the reinforcing bars in the block cores to satisfy the grout annulus requirement without lateral restrainers. To address this challenge, restrainer bar chairs can be used in the construction of RM walls which are easier to employ in comparison to lateral restrainer ties. However, the implications of adopting restrainer bar chairs as an alternative to restrainer ties in RM wall construction are not well verified. In this study, the influence of restrainer bar chairs and conventional lateral ties restraining methods on the axial compression and out-of-plane bending characteristics of RM walls have been investigated. In total, twelve RM walls of dimensions 1390 mm height × 590 mm length × 190 mm thickness were constructed and tested, of which, four walls each were tested under concentric and eccentric compression and four-point bending. The experimental results revealed that the performance of RM walls with restrainer bar chairs and conventional lateral ties were similar, in terms of the observed failure modes, strength, load–displacement characteristics obtained under both compression and out-of-plane loading conditions. Strain measurements on rebars indicated that a composite action was ensued in both restrainer configurations. The capacities of the RM walls under compression and out-of-plane bending were also verified with three different masonry standards provisions and were found adequate with reasonable safety. Overall, it can be concluded that the restrainer bar chairs can effectively be used in RM walls to enable quick and accurate vertical positioning of the rebars and ensure adequate grout annulus around them.